Visual Daun dan Identifikasi Hara Mikro pada Tanaman Lada dengan Kriteria Pertumbuhan Baik - Irman,; Nyayu Siti Khodijah,; Ismed Inonu,; Muntoro,; Iwan Setiawan, (Journal Galung Tropika, 2024)
Fertility and continuity of results are needed in pepper cultivation, so the right compatibility of nutrients is needed. Micronutrient observations are often not carried out regularly and tend to lag behind macronutrients, even though they are equally essential. Symptoms will be visible visually on the leaves and it is important to know that identifying nutrient symptoms is important. The leaf samples were represented by 20 old leaves and 20 young leaves which were observed visually by comparing them based on the nutrient symptom table, then the micronutrients of the young leaf tissue were analyzed. Based on the visuals of the leaves, symptoms of micronutrients were found dominantly found in young leaves. The diagnosis results based on visual symptoms were that pepper plants with the criteria for healthy growth still found symptoms of Fe deficiency in the form of yellowing in young leaves and also in old leaves, symptoms of Zn toxicity in the form of chlorosis between the leaves. young and Kahat B which shows that there are several young leaves which are also darker in color than normal young leaves. Based on analysis of the micro nutrient content found in young leaf tissue, the content of Cu, available Fe, Mn, Zn, B, Mo is below 100 ppm (100 mg/Kg), this figure shows that it is still in the low category.